Healthier by Precommitment. (February 2014) - Schwartz, Janet; Mochon, Daniel; Wyper, Lauren; Maroba, Josiase; Patel, Deepak; Ariely, Dan
We tested a voluntary self-control commitment device to help grocery shoppers make healthier food purchases. Participants, who were already enrolled in a large-scale incentive program that discounts the price of eligible groceries by 25%, were offered the chance to put their discount on the line. Agreeing households pledged that they would increase their purchases of healthy food by 5 percentage points above their household baseline for each of 6 months. If they reached that goal, their discount was awarded as usual; otherwise, their discount was forfeited for that month. Thirty-six percent of households that were offered the binding commitment agreed; they subsequently showed an average 3.5-percentage-point increase in healthy grocery items purchased in each of the 6 months; households that declined the commitment and control-group households that were given a hypothetical option to precommit did not show such an increase. These results suggest that self-aware consumers will seize opportunities to create restrictive choice environments for themselves, even at some risk of financial loss.